Determinants of delay in the diagnosis and treatment of suspected tuberculosis by HIV status in South Africa - Kanje, Victor (My University, 2017)
Introduction Delays in diagnosing and treating tuberculosis increase the risk of transmission, morbidity and mortality especially in low socio-economic settings with high HIV and TB rates. The aim of this study was to determine factors associated with the delay in the diagnosis and treatment of suspected TB by HIV status in hospitalised patients in South Africa. Methods This study was a secondary analysis of data from a three centre prospective cohort of inpatients recruited between 2006 and 2009 that were clinically diagnosed with active TB on admission. Results Data from 1018 patients (67% female) of a median age of 36 years (IQR: 30-44) with known HIV status were analysed: 875 (86%) positive and 143 (14%) negative. HIV positive patients had significantly longer median total delays relative to the negative (39 days, IQR: 28-74 vs. 32 days, IQR: 21-56; p<0.02). Unemployment, seeking prior treatment and use of cotrimoxazole predicted total delay in the HIV positive patients. Conclusion Patient delay is high in HIV positive patients compared to the HIV negative. Public health interventions targeting earlier diagnosis of TB disease in HIV positive patients should be enhanced.
A research report submitted to the School of Public Health, Faculty of Health Sciences, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Masters in Science in Epidemiology and Biostatistics June 2017
Keywords: Tuberculosis HIV